2018
DOI: 10.1162/jocn_a_01243
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neural Adaptation in Approach Behavior

Abstract: People often make approachability decisions based on perceived facial trustworthiness. However, it remains unclear how people learn trustworthiness from a population of faces and whether this learning influences their approachability decisions. Here we investigated the neural underpinning of approach behavior and tested two important hypotheses: whether the amygdala adapts to different trustworthiness ranges and whether the amygdala is modulated by task instructions and evaluative goals. We showed that partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 49 publications
2
18
2
1
Order By: Relevance
“…2007 ). On the other hand, in the present study, we found that the right amygdala showed flexible response to facial trustworthiness given different task instructions, in contrast to our prior report that the right amygdala’s response to trustworthiness is not modulated by stimulus range or social context ( Wang et al. 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2007 ). On the other hand, in the present study, we found that the right amygdala showed flexible response to facial trustworthiness given different task instructions, in contrast to our prior report that the right amygdala’s response to trustworthiness is not modulated by stimulus range or social context ( Wang et al. 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We used both linear and quadratic regressors in the modeling according to previous studies ( Todorov et al. 2008 ; Wang et al. 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proponents of both theoretical positions agree that at least some first impressions must be learned 11 , 17 23 . Evidence in favour of this claim comes from data showing that participants form first impressions from cultural cues that are the products of recent human history.…”
Section: Introductionmentioning
confidence: 99%
“…К настоящему времени в рамках изучения нейропроцессов в человеческом мозге накопилось значительное число эмпирических свидетельств того, что люди практически мгновенно, восприняв лицо другого человека, оценивают благонадежность последнего [Todorov, Pakrashi, Oosterhof, 2009;Olivola, Todorov, 2010]. Точность и достоверность такой оценки часто преувеличивается [Todorov et al, 2015], она подвержена различным влияниям [Aviezer et al, 2011;Posten, Ocken fels, Mussweiler, 2014] и уточняется в ходе социальных взаимодействий [Sparks, Burleigh, Barclay, 2016;van der Werff, Buckley, 2017;Verosky et al, 2018;Wang et al, 2018]. Способность формировать такие оценки выработалась в ходе эволюции человека: ведь для людей эффективное кооперативное взаимодействие является важнейшим условием выживания [Tomasello et al, 2012;Tomasello, Vaish, 2013;Rand, 2016].…”
Section: порождающий подход к трактовке доверияunclassified